1998
DOI: 10.1111/j.2042-7158.1998.tb04013.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effects of Sparteine, Lupanine and Lupin Extract on the Central Nervous System of the Mouse

Abstract: Lupin is toxic because of its alkaloid content, sparteine and lupanine in particular. Although the pharmacological properties of sparteine are well known those of lupanine have not been much studied. This paper reports procedures for extraction, purification and crystallization of lupanine, and methods for the preparation of an extract for injection of Lupinus mutabilis Sweet, and for the determination of the acute toxicity and maximum non-lethal dose (DL0) of lupanine, sparteine and lupin extract in the mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 7 publications
1
32
0
1
Order By: Relevance
“…These findings are consistent with the results reported by Pothier et al (1998) for animals treated with Sp (13 mg/kg, i.p.) 30 min before PTZ (125 mg/kg, s.c.) administration, where Sp delayed the onset of convulsive behavior and prolonged the survival time.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…These findings are consistent with the results reported by Pothier et al (1998) for animals treated with Sp (13 mg/kg, i.p.) 30 min before PTZ (125 mg/kg, s.c.) administration, where Sp delayed the onset of convulsive behavior and prolonged the survival time.…”
Section: Discussionsupporting
confidence: 95%
“…In this respect, Sp is a QA obtained from most Lupine species (Wink, 1992(Wink, , 1993a. The role of Sp as an anticonvulsant drug was first observed in the PTZ model (Pothier et al, 1998), but subsequent studies have not been conducted until the present work.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…They are metabolites synthesized by lupin plants and other species of the Genisteae family as a defense mechanism against insects and herbivores [10]. In mammals, QA intoxication is characterized by trembling, shaking, excitation, and convulsion [11]. The majority of acute toxicity studies were performed on lupanine and sparteine, the most common QAs: both showed moderate acute oral toxicity due to neurological effects leading to the loss of motor co-ordination and muscular control [12].…”
Section: Introductionmentioning
confidence: 99%